How uncivil customers corrode the relationship between frontline employees and retailers. (January 2019) - Gaucher, Benoît; Chebat, Jean-Charles
Abstract: This study investigates the effects of customers' uncivil treatments on frontline retail employees' emotions, deviant behaviors and relationship with the retail organization. Our theoretical model is based on both marketing and personnel management literatures. 415 frontline retailing American employees answered our questionnaire. Employees treated uncivilly by customers feel angry but have to hide their negative emotions, which leads them to emotional exhaustion and deviant behaviors. Paradoxically, employees' strong commitment to their retailing organization brings about more deviant behaviors. We propose some managerial strategies to cope with uncivil customers, as well as future research on this important and under-researched topic.